2018
DOI: 10.1177/2331216518814388
|View full text |Cite
|
Sign up to set email alerts
|

Improving Speech Intelligibility by Hearing Aid Eye-Gaze Steering: Conditions With Head Fixated in a Multitalker Environment

Abstract: The behavior of a person during a conversation typically involves both auditory and visual attention. Visual attention implies that the person directs his or her eye gaze toward the sound target of interest, and hence, detection of the gaze may provide a steering signal for future hearing aids. The steering could utilize a beamformer or the selection of a specific audio stream from a set of remote microphones. Previous studies have shown that eye gaze can be measured through electrooculography (EOG). To explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In contrast, in a proof-of-concept study (Favre-Félix et al, 2018) recently demonstrated the potential of improving speech intelligibility in HI people in real time by assessing visual attention via EOG. Although the results of Favre-Félix et al (2018) provided first insights into visual attention steering via EOG, the study had substantial limitations regarding its potential value for applicability in HA technology. In that study, EOG was obtained from electrodes placed on the temples, which would not be feasible in real-life applications, where the sensors should preferably be embedded in the earmold.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, in a proof-of-concept study (Favre-Félix et al, 2018) recently demonstrated the potential of improving speech intelligibility in HI people in real time by assessing visual attention via EOG. Although the results of Favre-Félix et al (2018) provided first insights into visual attention steering via EOG, the study had substantial limitations regarding its potential value for applicability in HA technology. In that study, EOG was obtained from electrodes placed on the temples, which would not be feasible in real-life applications, where the sensors should preferably be embedded in the earmold.…”
Section: Introductionmentioning
confidence: 98%
“…While it has been shown that attended sound sources can be decoded from cortical brain responses via a correlation analysis of the scalp responses and an envelope representation of the attended input sound stream, a robust estimate requires several seconds of decoding, which is not applicable for real-time steering (Fuglsang et al, 2017;Dau et al, 2018). In contrast, in a proof-of-concept study (Favre-Félix et al, 2018) recently demonstrated the potential of improving speech intelligibility in HI people in real time by assessing visual attention via EOG. Although the results of Favre-Félix et al (2018) provided first insights into visual attention steering via EOG, the study had substantial limitations regarding its potential value for applicability in HA technology.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking head motion from only one ear might not give precise enough results, especially considering the absence of external reference points, such as a magnetometer. As having more fine grained data points enhances the precision of the estimation, we combined the streams of inertial data coming from the IMU sensors in the two earbuds 5 . We leverage the assumption that the two different IMUs are recording, from different vantage points, the same rotation.…”
Section: Head Tracking Methodologymentioning
confidence: 99%
“…Previous studies, especially from the medical community, highlight the importance of using directional hearing-aids leveraging the visual attention of the user [5,14]. For example, Favre-Félix et al [5] use electrooculography data (EOG) to characterize the visual attention of the patients. Their study shows how steering an hearing-aid by using EOG leads to better performance on the sentence correctness score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation